Mephedrone and 3, 4-methylenedioxy-methamphetamine: Comparative psychobiological effects as reported by recreational polydrug users. (December 2016) - Jones, Lewis; Reed, Phil; Parrott, Andrew
Aims: The purpose of this study was to compare the effects of mephedrone and 3, 4-methylenedioxy-methamphetamine (MDMA), as reported by young recreational polydrug users. Methods: 152 MDMA users and 81 mephedrone users were recruited through snowballing on social network sites. They completed a standard online questionnaire for either mephedrone or MDMA. The questions covered the average amount taken per session, the longest duration of usage in the last 12-months, subjective effects while on-drug, and recovery effects in the days afterwards. Results: Mephedrone users reported a significantly longer maximum session of use than MDMA users. Mephedrone users also reported a significantly greater average amount used per session. The majority of on-drug subjective ratings did not differ between drugs, with similar increases in entactogenic effects. Although mephedrone users did report significantly more frequent issues with sleeping, anger and anxiety. In relation to recovery, mephedrone users reported more frequent craving, nasal irritation, paranoia, and relationship difficulties. Mephedrone users also rated general recovery effects as more severe over the seven-day period following use, taking more days to feel normal. Conclusions: The acute effects of MDMA and mephedrone were broadly similar. However, the recovery period for mephedrone was more enduring, possibly due to the longer duration of acute session usage.